Іонообмінні та адсорбційні властивості шунгіту та сапоніту в умовах хімічного моделювання шлунково-кишкового тракту людини - Яновська, Е.С.; Затовський, І.В.; Марценюк, О.Б.; Пліш, Б.А. (Видавничий дім "Академперіодика" НАН України, 2007)
Ion-exchange properties of shungit (Kareliya, Russia) and saponit clay (Khmelnytskii region, Ukraine) under conditions of the chemical modeling of human stomach (0.1 М HCl) and intestine (solution of NaHCO3, pH 8.5) are analyzed by IR-spectroscopy and X-ray fluorescence methods. Adsorption of lead (ІІ), zinc (ІІ), manganese (ІІ), iron (III), copper (II), and cadmium (ІІ) is studied by flame-adsorption and X-ray fluorescence methods under selected conditions. It is proved that these minerals are safe and useful as the filling agents of alimentary components and medicinal preparations from the chemical point of view.